Complexes of Co(II), Ni(II) and Cu(II) with 3-Phenyl Quinazoline-4(3H)-One Carboxaldehyde Semicarbazone and Thiosemicarbazone - Rai, B.K. (Asian Journal of Chemistry, 2010)
Complexes of 3-phenyl quinazoline 4(3H) one carboxaldehyde semicarbazone (PQCASC) and 3-phenyl quinazolien 4(3H) one carbox aldehyde thiosemicarbazone (PQCATSC) with bivalent metal ion of composition [M(PQCASC)2]X2 and [M(PQCATSC)2]X2, M = Co(II), Ni(II) and Cu(II) and X = Cl–, Br– or I– have been prepared and characterised on the basis of elemental analysis, IR spectra, electronic spectra, magnetic susceptibility and conductivity measurements and are found to be octahedral in geometry. The complexes are found to be electrolytic in nature of 1 : 2 type.